2017
DOI: 10.1016/j.ijcard.2017.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Nardilysin is a promising biomarker for the early diagnosis of acute coronary syndrome

Abstract: NRDC is a promising biomarker for the early detection of ACS, even in UA patients without elevation of necrosis markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 23 publications
0
28
1
Order By: Relevance
“…NRDC in macrophages regulates arthritis via the control of TNFa secretion because the macrophage-specific deletion of NRDC markedly ameliorated arthritis (31). We also demonstrated that inflammatory cells infiltrating the infarcted myocardium strongly express NRDC (25). However, clinical data from this study do not strongly support this hypothesis because preoperative C-reactive protein levels in ICC patients did not correlate with serum NRDC levels (data not shown).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…NRDC in macrophages regulates arthritis via the control of TNFa secretion because the macrophage-specific deletion of NRDC markedly ameliorated arthritis (31). We also demonstrated that inflammatory cells infiltrating the infarcted myocardium strongly express NRDC (25). However, clinical data from this study do not strongly support this hypothesis because preoperative C-reactive protein levels in ICC patients did not correlate with serum NRDC levels (data not shown).…”
Section: Discussionmentioning
confidence: 67%
“…Serum was isolated from whole blood and stored at À80 C until analyzed. To quantify serum NRDC levels, an enzyme-linked immunosorbent assay (ELISA) was performed according to a previously described method (25). Briefly, to establish a sandwich ELISA system, all combinations of the 7 monoclonal antibodies for NRDC were tested, and the optimum combination of clone #231 for coating and #304 for detection was selected.…”
Section: Measurement Of Serum Nrdc Levelsmentioning
confidence: 99%
“…We examined the levels of antibodies against the bPRCP-214 peptide in sera of HDs and patients with DM or CVD, using the supersensitive and stable AlphaLISA method [23][24][25][26][27][28][29][30][31]. All serum samples were obtained from Chiba University Hospital.…”
Section: Elevation Of Serum Antibody Levels Against Prcp In Patients mentioning
confidence: 99%
“…We also identified the following autoantibody-recognized antigens by recombinant cDNA expression cloning (SEREX) method or protein array method: TACSTD2 [12], TRIM21 [13], SLC2A1 [14], MKRN1 [15], ECSA [16], and CCNL2 [17] in esophageal squamous cell carcinoma; FIR/PUF60 in colon carcinoma [18]; SH3GL1 [19] and filamin C [20] in low-grade glioma; TLN1 in multiple sclerosis [21]; RPA2 [22] and SOSTDC1 [23] in ischemic stroke; NRD1 in acute coronary syndrome [24]; TUBB2C [25], GADD34 [26], and adiponectin [27] in DM; COPE in obstructive sleep apnea [28]; and ATP2B4 [29], BMP-1 [22,29], DHPS [30], and SH3BP5 [31] in arteriosclerosis-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Despite of the increased successful treatment rates of STEMI patients, they are still confronted with worse prognosis after the incidence of STEMI, including heart failure, recurrence of STEMI, and other complications (3). Multiple tools have been developed to evaluate the risk and predict the prognosis of patients with STEMI, including comprehensive score system and biomarkers, such as SYNTAX score (4), glycated hemoglobin (5), Nardilysin (6) and other biomarkers. However, relative less accuracy and focus on early prognosis have limited the application of those biomarkers and risk stratification, which necessitates more studies to evaluate the value of novel biomarkers in predicting the long-term prognosis of STEMI.…”
Section: Introductionmentioning
confidence: 99%